Preparation process of composite plastic woven cloth
By grafting the polyester flame retardant to the surface of silica and blending it with PET polyester, composite PET flat wire is prepared, which solves the problem of poor mechanical properties and flame retardant properties of PET flat wire and its braided fabric, achieving higher mechanical properties and wear resistance, and significantly improving flame retardant properties.
Patent Information
- Application Number
- CN202510228288.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-28
AI Technical Summary
The mechanical properties and flame retardancy of PET flat wire and its woven fabrics are poor.
Compound PET flat wires were prepared by grafting the polyester flame retardant to the surface of silica and melt blending with polyethylene terephthalate, and finally woven into a composite plastic woven fabric through a braiding machine.
The tensile force, elongation of breakage and wear resistance of PET flat wire and its braided fabric is significantly improved, while enhancing its flame retardant performance.
Smart Images

Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of woven cloth, in particular to a preparation process of a composite plastic woven cloth. Background Art
[0002] Woven cloth is mainly made of PET polyethylene terephthalate, polyethylene and other flat yarns through weaving and other processes. It has important applications in civil engineering, water conservancy, construction engineering and other fields. Developing high-performance PET flat yarns and plastic woven cloths to give them flame retardant, wear-resistant and other properties is a research hotspot. Flame retardants are functional additives, mainly used in plastics, textiles, rubber and other materials. Additive flame retardants are directly physically blended with the material matrix, which is very simple to operate. However, additive flame retardants will affect the mechanical properties of the polymer material matrix, so it is necessary to improve the compatibility between the flame retardant and the material matrix.
[0003] Nano-silicon dioxide is an inorganic nano-material with high specific surface area, high mechanical strength, strong wear resistance and easy surface organic modification. Patent CN117431682A discloses that 2,3,5,5,5-pentachloro-4-oxo-pentenoic acid mesoporous silica microspheres are mixed and spun with polyethylene terephthalate and finally woven with nylon fibers. The resulting tensile mesh has the advantages of good waterproofness, tensile resistance and antibacterial properties. Compared with the tensile mesh of the invention, the present invention uses polyester flame retardant grafted with silica to improve the wear resistance and flame retardancy of PET flat yarn and its woven cloth. Summary of the invention
[0004] The invention solves the problem that the PET flat yarn and the woven fabric thereof have poor mechanical properties and flame retardancy.
[0005] The technical solution of the present invention is a preparation process of a composite plastic woven cloth, wherein the composite plastic woven cloth is woven by a composite PET flat wire through a weaving machine.
[0006] The preparation process of composite PET flat yarn is: Step S1, add succinic acid-based DOPO, bishydroxyethyl imidazole intermediate, and p-toluenesulfonic acid in a molar ratio of 1: (1.05-1.1): (0.05-0.07) to N,N-dimethylformamide, stir to dissolve, heat to 150-155°C, react for 10-15h, condense and reflux during the reaction; after cooling, pour the solution into ethanol, filter, wash with ethanol and dichloromethane in turn, and dry to obtain a polyester flame retardant. The reaction formula is: .
[0007] Step S2, adding polyester flame retardant to N,N-dimethylformamide, stirring, adding TDI modified silica and dibutyltin dilaurate, wherein the mass ratio of polyester flame retardant, TDI modified silica and dibutyltin dilaurate is (0.3-0.8):1:(0.002-0.006); heating to 80-90°C, reacting for 6-10h, cooling, pouring the solution into ethanol, filtering, washing with ethanol, and drying to obtain polyester flame retardant grafted silica.
[0008] Step S3, adding 100 parts by weight of polyethylene terephthalate and 0.5-4 parts by weight of polyester flame retardant grafted silica into a twin-screw extruder for melt blending and extrusion; then forming a film sheet through a cast film machine; finally dividing into embryonic filaments through a flat yarn machine, stretching and shaping, and obtaining a composite PET flat yarn.
[0009] Preferably, in step S3, the temperature of each section of the twin-screw extruder is 160-280°C, and the screw speed is 100-150r / min; the temperature of each section of the cast film machine is 265-290°C, and the screw speed is 80-100r / min; the temperature during stretching is 95-100°C, and the stretching ratio is 4.5-5.5.
[0010] Preferably, the preparation process of the bishydroxyethyl imidazole intermediate is: add 2-(1H-imidazole-5-yl)ethanol (CAS No. 872-82-2), 1,4-di(bromomethyl)benzene (CAS No. 623-24-5), and potassium carbonate in a molar ratio of (2-2.4):1:(2.2-2.8) to acetonitrile or tetrahydrofuran solvent, heat to 40-50°C, stir to react for 12-18h, distill under reduced pressure, wash with water, dissolve the product in ethanol, heat to volatilize and precipitate, then cool and recrystallize in an ice-water bath to obtain the bishydroxyethyl imidazole intermediate. The reaction formula is: .
[0011] Preferably, the preparation process of TDI modified silica is: add 100 parts by weight of nano-silica to toluene, disperse by ultrasonic, add 60-100 parts by weight of toluene-2,4-diisocyanate, heat to 80-90°C, react for 2-3h, filter, wash with toluene, and dry to obtain TDI modified silica.
[0012] Technical effect: The present invention utilizes 2-(1H-imidazole-5-yl)ethanol and 1,4-di(bromomethyl)benzene for substitution reaction, and then carries out esterification polymerization reaction with succinic acid-based DOPO to obtain a polyester flame retardant, and then utilizes its terminal hydroxyl group to react with the isocyanate group on the surface of TDI-modified silica, thereby grafting the polyester flame retardant onto the surface of nano-silica, and grafting the polyester flame retardant onto silica.
[0013] The invention carries out melt blending, segmentation into embryonic yarns, stretching, shaping and other processes on polyethylene terephthalate and polyester flame retardant grafted silica, and weaves them through a weaving machine to obtain composite PET flat yarn and plastic woven cloth thereof; the polyester flame retardant contains polyester molecular chains and has good compatibility with PET polyester; after being grafted and modified by the polyester flame retardant, nano silica has better compatibility in the PET flat yarn and excellent dispersibility, significantly improves the tensile strength and elongation at break of the PET flat yarn, reduces the wear quality loss of the woven cloth, and exhibits higher mechanical properties and wear resistance.
[0014] The polyester flame retardant of the invention contains DOPO phosphate and biimidazole groups to form a nitrogen-phosphorus flame retardant, which has a good synergistic flame retardant effect with nano-silicon dioxide, significantly improves the limiting oxygen index of the PET plastic woven fabric, and has better flame retardant performance. DETAILED DESCRIPTION
[0015] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described in detail below in conjunction with specific embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0016] The preparation process of succinic acid-DOPO is as follows: add 30 mL of xylene, 30 mL of tetrahydrofuran, and 10 g of DOPO 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to a flask containing a condenser reflux tube, introduce nitrogen, heat to 95°C, add 5.37 g of maleic acid dropwise after stirring, react for 10 hours, cool and filter, wash the product with a mixed solution of tetrahydrofuran and xylene, and dry to obtain succinic acid-DOPO. The structural formula is .
[0017] Example 1 (1) Add 14.4 mmol of 2-(1H-imidazole-5-yl)ethanol, 6 mmol of 1,4-di(bromomethyl)benzene and 16.8 mmol of potassium carbonate to 30 mL of acetonitrile solvent, heat to 40°C, stir and react for 18 hours, distill under reduced pressure, wash with water, dissolve the product in ethanol, heat to evaporate and precipitate, then cool in an ice-water bath and recrystallize to obtain a bis(hydroxyethyl)imidazole intermediate.
[0018] (2) Add 0.5 g of nano-silica to 10 mL of toluene, disperse by ultrasonication, add 0.3 g of toluene-2,4-diisocyanate, heat to 80 °C, react for 3 h, filter, wash with toluene, and dry to obtain TDI-modified silica.
[0019] (3) Add 10 mmol of succinic acid-based DOPO, 11 mmol of bis(hydroxyethyl)imidazole intermediate, and 0.6 mmol of p-toluenesulfonic acid to 50 mL of N,N-dimethylformamide, stir to dissolve, heat to 155°C, and react for 10 h. Condensation and reflux are performed during the reaction. After cooling, the solution is poured into ethanol, filtered, washed with ethanol and dichloromethane in turn, and dried to obtain a polyester flame retardant.
[0020] (4) Add 0.15 g of polyester flame retardant to 40 mL of N,N-dimethylformamide, stir, add 0.5 g of TDI-modified silica (prepared according to the method of Example 1) and 1 mg of dibutyltin dilaurate, heat to 80°C, react for 8 h, cool, pour the solution into ethanol, filter, wash with ethanol, and dry to obtain polyester flame retardant grafted silica.
[0021] (5) Add 1000g of polyethylene terephthalate and 5g of polyester flame retardant grafted silica into a twin-screw extruder for melt blending and extrusion. The temperature of each section is 160°C, 210°C, 255°C, 270°C, 280°C, and 280°C, and the screw speed is 100r / min; then, a film sheet is formed by a cast film machine. The temperature of each section is 265°C, 275°C, 295°C, 290°C, and 285°C, and the screw speed is 100r / min; finally, the film is divided into embryonic filaments by a flat yarn machine, stretched, and shaped. The temperature during stretching is 100°C and the stretching multiple is 5; thereby obtaining a composite PET flat yarn.
[0022] Example 2 (1) Add 12 mmol of 2-(1H-imidazole-5-yl)ethanol, 6 mmol of 1,4-di(bromomethyl)benzene and 13.2 mmol of potassium carbonate to 25 mL of tetrahydrofuran solvent, heat to 50°C, stir and react for 12 h, evaporate under reduced pressure, wash with water, dissolve the product in ethanol, heat to evaporate and precipitate, then cool in an ice-water bath and recrystallize to obtain a bis(hydroxyethyl)imidazole intermediate.
[0023] (2) Add 0.5 g of nano-silica to 12 mL of toluene, disperse by ultrasonication, add 0.5 g of toluene-2,4-diisocyanate, heat to 90 °C, react for 2 h, filter, wash with toluene, and dry to obtain TDI-modified silica.
[0024] (3) Add 10 mmol of succinic acid-based DOPO, 11 mmol of bis(hydroxyethyl)imidazole intermediate, and 0.5 mmol of p-toluenesulfonic acid to 60 mL of N,N-dimethylformamide, stir to dissolve, heat to 155°C, and react for 15 h. Condensation and reflux are performed during the reaction. After cooling, the solution is poured into ethanol, filtered, washed with ethanol and dichloromethane in turn, and dried to obtain a polyester flame retardant.
[0025] (4) Add 0.4 g of polyester flame retardant to 60 mL of N,N-dimethylformamide, stir, add 0.5 g of TDI-modified silica and 3 mg of dibutyltin dilaurate, heat to 80 °C, react for 10 h, cool, pour the solution into ethanol, filter, wash with ethanol, and dry to obtain polyester flame retardant grafted silica.
[0026] (5) Add 1000g of polyethylene terephthalate and 20g of polyester flame retardant grafted silica into a twin-screw extruder for melt blending and extrusion. The temperature of each section is 160°C, 210°C, 255°C, 270°C, 280°C, and 280°C, and the screw speed is 150r / min; then, a film sheet is formed by a cast film machine. The temperature of each section is 265°C, 275°C, 295°C, 290°C, and 285°C, and the screw speed is 100r / min; finally, the film is divided into embryonic yarns, stretched, and shaped by a flat yarn machine. The stretching temperature is 100°C and the stretching multiple is 4.5; and a composite PET flat yarn is obtained.
[0027] Example 3 (1) Add 10 mmol of succinic acid-based DOPO, 10.5 mmol of bis(hydroxyethyl)imidazole intermediate (prepared according to the method of Example 1), and 0.7 mmol of p-toluenesulfonic acid to 50 mL of N,N-dimethylformamide, stir to dissolve, heat to 150°C, and react for 10 hours. During the reaction, condense and reflux; after cooling, pour the solution into ethanol, filter, wash with ethanol and dichloromethane in turn, and dry to obtain a polyester flame retardant.
[0028] (2) Add 0.28 g of polyester flame retardant to 40 mL of N,N-dimethylformamide, stir, add 0.5 g of TDI-modified silica and 2.2 mg of dibutyltin dilaurate, heat to 90 °C, react for 6 h, cool, pour the solution into ethanol, filter, wash with ethanol, and dry to obtain polyester flame retardant grafted silica.
[0029] (3) Add 1000g of polyethylene terephthalate and 40g of polyester flame retardant grafted silica into a twin-screw extruder for melt blending and extrusion. The temperature of each section is 160°C, 210°C, 255°C, 270°C, 280°C, and 280°C, and the screw speed is 100r / min; then, a film sheet is formed by a cast film machine. The temperature of each section is 265°C, 275°C, 295°C, 290°C, and 285°C, and the screw speed is 80r / min; finally, the film is cut into embryonic yarns by a flat yarn machine, stretched, and shaped. The temperature during stretching is 95°C and the stretching multiple is 5.5; and a composite PET flat yarn is obtained.
[0030] Comparative Example 1 (1) Add 1000g of polyethylene terephthalate into a twin-screw extruder for melting and extrusion, with the temperatures of each section being 160°C, 210°C, 255°C, 270°C, 280°C, and 280°C, and the screw speed being 100r / min; then form a film sheet through a cast film machine, with the temperatures of each section being 265°C, 275°C, 295°C, 290°C, and 285°C, and the screw speed being 100r / min; finally, the film is cut into embryonic filaments through a flat yarn machine, stretched, and shaped, with the stretching temperature being 100°C and the stretching multiple being 5; and a composite PET flat yarn is obtained.
[0031] Comparative Example 2 (1) Stir and mix 10 mmol of succinic acid-based DOPO and 11 mmol of bis(hydroxyethyl)imidazole intermediate to obtain a composite flame retardant.
[0032] (2) Add 1000g of polyethylene terephthalate and 5g of the composite flame retardant into a twin-screw extruder for melt blending and extrusion. The temperature of each section is 160°C, 210°C, 255°C, 270°C, 280°C, and 280°C, and the screw speed is 100r / min; then, a film sheet is formed by a cast film machine. The temperature of each section is 265°C, 275°C, 295°C, 290°C, and 285°C, and the screw speed is 100r / min; finally, the film is divided into embryonic yarns, stretched, and shaped by a flat yarn machine. The temperature during stretching is 100°C and the stretching multiple is 5; thereby obtaining a composite PET flat yarn.
[0033] Comparative Example 3 (1) 1000 g of polyethylene terephthalate and 5 g of polyester flame retardant (prepared according to the method of Example 1) were added to a twin-screw extruder for melt blending and extrusion, with the temperatures of each section being 160°C, 210°C, 255°C, 270°C, 280°C, and 280°C, and the screw speed being 100 r / min; then a film was formed by a cast film machine, with the temperatures of each section being 265°C, 275°C, 295°C, 290°C, and 285°C, and the screw speed being 100 r / min; finally, the film was divided into embryonic filaments by a flat yarn machine, stretched, and shaped, with the stretching temperature being 100°C and the stretching multiple being 5; and a composite PET flat yarn was obtained.
[0034] Comparative Example 4 (1) 1000 g of polyethylene terephthalate and 5 g of TDI-modified silica (prepared according to the method of Example 1) were added to a twin-screw extruder for melt blending and extrusion, with the temperatures of each section being 160°C, 210°C, 255°C, 270°C, 280°C, and 280°C, and the screw speed being 100 r / min; then a film was formed by a cast film machine, with the temperatures of each section being 265°C, 275°C, 295°C, 290°C, and 285°C, and the screw speed being 100 r / min; finally, the film was divided into embryonic filaments by a flat yarn machine, stretched, and shaped, with the temperature during stretching being 100°C and the stretching multiple being 5; and a composite PET flat yarn was obtained.
[0035] Comparative Example 5 (1) Add 0.15 g of polyester flame retardant (prepared according to the method of Example 1) to 40 mL of N,N-dimethylformamide, stir, add 0.5 g of nano-silicon dioxide and 1 mg of dibutyltin dilaurate, heat to 80°C, stir and mix for 8 hours, cool, pour the solution into ethanol, filter, wash with ethanol, and dry to obtain polyester flame retardant-silicon dioxide.
[0036] (2) Add 1000g of polyethylene terephthalate and 5g of polyester flame retardant-silicon dioxide into a twin-screw extruder for melt blending and extrusion, with the temperature of each section being 160°C, 210°C, 255°C, 270°C, 280°C, and 280°C, and the screw speed being 100r / min; then form a film sheet through a cast film machine, with the temperature of each section being 265°C, 275°C, 295°C, 290°C, and 285°C, and the screw speed being 100r / min; finally, divide it into embryonic filaments through a flat yarn machine, stretch it, and shape it, with the temperature during stretching being 100°C and the stretching multiple being 5; and obtain a composite PET flat yarn.
[0037] Comparative Example 6 (1) Add 10 mmol of succinic acid-DOPO, 11 mmol of ethylene glycol, and 0.6 mmol of p-toluenesulfonic acid to 50 mL of N,N-dimethylformamide, stir to dissolve, heat to 155°C, and react for 10 hours. Condensation and reflux are performed during the reaction. After cooling, the solution is poured into ethanol, filtered, washed with ethanol and dichloromethane in turn, and dried to obtain a polyester flame retardant.
[0038] (2) Add 0.15 g of polyester flame retardant to 40 mL of N,N-dimethylformamide, stir, add 0.5 g of TDI-modified silica and 1 mg of dibutyltin dilaurate, heat to 80 °C, react for 8 h, cool, pour the solution into ethanol, filter, wash with ethanol, and dry to obtain polyester flame retardant grafted silica.
[0039] (3) Add 1000g of polyethylene terephthalate and 5g of polyester flame retardant grafted silica into a twin-screw extruder for melt blending and extrusion. The temperature of each section is 160°C, 210°C, 255°C, 270°C, 280°C, and 280°C, and the screw speed is 100r / min; then, a film sheet is formed by a cast film machine. The temperature of each section is 265°C, 275°C, 295°C, 290°C, and 285°C, and the screw speed is 100r / min; finally, the film is divided into embryonic yarns, stretched, and shaped by a flat yarn machine. The stretching temperature is 100°C and the stretching multiple is 5; and a composite PET flat yarn is obtained.
[0040] The mechanical properties of PET flat yarn were tested using an electronic fabric strength tester with a clamping distance of 200 mm and a tensile speed of 50 mm / min. Each sample was tested 5 times and the average value was taken.
[0041] The PET flat yarn is woven into plastic woven cloth through a weaving machine.
[0042] According to GB T 5454-1997 method, the oxygen index tester is used to test the limiting oxygen index of plastic woven fabric. The larger the limiting oxygen index, the better the flame retardancy.
[0043] The wear resistance of plastic woven fabric was tested using a friction and wear tester. The counterpiece was a 45# steel ring, the load was 1kg, the speed was 200r / min, and the wear time was 10min. The mass loss before and after wear was tested. The smaller the wear mass loss, the better the wear resistance.
[0044] Table 1 Breaking force (N) Elongation at break (%) Limiting oxygen index (%) Wear mass loss (mg) Example 1 45.2 63.1 26.4 50.6 Example 2 52.3 76.8 28.5 39.8 Example 3 50.5 62.7 29.8 32.0 Comparative Example 1 37.3 52.9 20.8 58.4 Comparative Example 2 34.1 48.5 25.3 61.7 Comparative Example 3 37.6 52.4 25.5 58.5 Comparative Example 4 43.7 61.9 21.3 51.1 Comparative Example 5 39.2 56.0 26.3 55.4 Comparative Example 6 45.0 63.6 25.2 50.9 The PET flat yarn and plastic woven fabric of Comparative Example 1 do not have polyester flame retardant grafted silica added, and have low tensile strength and elongation at break, large wear mass loss, poor mechanical properties and wear resistance, and a limiting oxygen index of only 20.8%, with poor flame retardancy.
[0045] In Example 1-3, polyester flame retardant grafted silica is added. The polyester flame retardant contains polyester molecular chains and has good compatibility with PET polyester. After the nano-silica is grafted and modified by the polyester flame retardant, it has better compatibility in the PET flat yarn and excellent dispersibility, which is beneficial to improve the mechanical properties and wear resistance of the PET flat yarn and its woven fabric, showing higher tensile strength, elongation at break and lower wear mass loss. At the same time, the polyester flame retardant contains DOPO phosphate and biimidazole groups to form a nitrogen-phosphorus flame retardant, which has a good synergistic flame retardant effect with the nano-silica, significantly improving the limiting oxygen index of the PET plastic woven fabric, and having better flame retardant properties.
[0046] Comparative Example 2 added a composite flame retardant composed of a blend of succinic acid-based DOPO and a bishydroxyethyl imidazole intermediate, which does not contain a polyester molecular chain and has poor compatibility with PET, which has a great impact on the mechanical properties of the PET flat yarn, with a significant decrease in breaking force and elongation at break, an increase in wear mass loss, and poor mechanical properties and wear resistance. In addition, no nano-silicon dioxide was added, resulting in a lower limiting oxygen index than that of each embodiment.
[0047] Comparative Example 3 adds a polyester flame retardant, which has good compatibility with PET polyester and has almost no effect on the mechanical properties of the PET flat yarn and the woven cloth. Its tensile strength, elongation at break and wear mass loss are very similar to those of Comparative Example 1, and still maintains good mechanical properties. However, Comparative Example 3 does not add silica, resulting in mechanical properties, wear resistance, and flame retardancy lower than those of the embodiments.
[0048] Comparative Example 4 adds TDI modified silica, and after the nano silica is modified by toluene-2,4-diisocyanate, the compatibility between the nano silica and PET polyester is also good, and the mechanical properties and wear resistance of the PET flat yarn and woven cloth are also improved to a certain extent, but the tensile strength and elongation at break are lower than those of the embodiments, which may be because the polyester flame retardant has better compatibility with the PET polyester than toluene-2,4-diisocyanate, and can better improve the compatibility and dispersibility of the nano silica in the PET flat yarn. In addition, the nano silica surface of Comparative Example 4 is not grafted with a polyester flame retardant, and the limiting oxygen index of the PET plastic woven cloth is low, and the flame retardancy is poor.
[0049] The nano-silica in Comparative Example 5 has not been modified with toluene-2,4-diisocyanate, and does not contain isocyanate groups on the surface, so it cannot react with the terminal hydroxyl groups of the polyester flame retardant, resulting in no grafting of the polyester flame retardant on the surface of the nano-silica, poor compatibility with PET polyethylene terephthalate, poor dispersibility in PET flat yarn and woven cloth, and failure to improve its mechanical properties and wear resistance.
[0050] In Comparative Example 6, ethylene glycol is used instead of the bis(hydroxyethyl)imidazole intermediate to carry out an esterification polymerization reaction with succinic acid-based DOPO. The obtained polyester flame retardant does not contain imidazole groups and cannot form a nitrogen-phosphorus flame retardant with DOPO, resulting in the limiting oxygen index of the PET plastic woven fabric being lower than that of the various embodiments, and the flame retardancy is poor.
[0051] The embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A process for preparing a composite plastic woven fabric, characterized in that: The composite plastic woven cloth is woven from composite PET flat yarns through a weaving machine; The preparation process of the composite PET flat yarn is: Step S1, adding succinate-based DOPO to N,N-dimethylformamide, the structural formula is The intermediate of bis(hydroxyethyl)imidazole and p-toluenesulfonic acid are stirred and dissolved, reacted, and after cooling, the solution is poured into ethanol, filtered, washed, and dried to obtain a polyester flame retardant; Step S2, adding polyester flame retardant to N,N-dimethylformamide, stirring, adding TDI modified silica and dibutyltin dilaurate, reacting, cooling, pouring the solution into ethanol, filtering, washing, and drying to obtain polyester flame retardant grafted silica; Step S3, adding 100 parts by weight of polyethylene terephthalate and 0.5-4 parts by weight of polyester flame retardant grafted silica into a twin-screw extruder for melt blending and extrusion; then forming a film sheet through a cast film machine; finally dividing into embryonic filaments through a flat yarn machine, stretching and shaping, and obtaining a composite PET flat yarn.
2. The process for preparing the composite plastic woven fabric according to claim 1, characterized in that: In the step S1, the molar ratio of succinic acid-based DOPO, bis(hydroxyethyl)imidazole intermediate, and p-toluenesulfonic acid is 1:(1.05-1.1):(0.05-0.07).
3. The process for preparing the composite plastic woven fabric according to claim 1, characterized in that: The reaction temperature in step S1 is 150-155° C., and the reaction time is 10-15 hours.
4. The process for preparing the composite plastic woven fabric according to claim 1, characterized in that: In the step S2, the mass ratio of the polyester flame retardant, TDI-modified silica, and dibutyltin dilaurate is (0.3-0.8):1:(0.002-0.006).
5. The process for preparing the composite plastic woven fabric according to claim 1, characterized in that: The reaction temperature in step S2 is 80-90° C., and the reaction time is 6-10 h.
6. The process for preparing the composite plastic woven fabric according to claim 1, characterized in that: In step S3, the temperature of each section of the twin-screw extruder is 160-280°C, and the screw speed is 100-150r / min; the temperature of each section of the cast film machine is 265-290°C, and the screw speed is 80-100r / min; the temperature during stretching is 95-100°C, and the stretching ratio is 4.5-5.
5.
7. The process for preparing the composite plastic woven fabric according to claim 2, characterized in that: The preparation process of the bishydroxyethyl imidazole intermediate is as follows: adding 2-(1H-imidazole-5-yl)ethanol, 1,4-di(bromomethyl)benzene and potassium carbonate in a molar ratio of (2-2.4):1:(2.2-2.8) to a solvent, heating to 40-50° C., stirring for reaction for 12-18 hours, distilling under reduced pressure, washing and recrystallizing to obtain the bishydroxyethyl imidazole intermediate.
8. The process for preparing the composite plastic woven fabric according to claim 7, characterized in that: The solvent is acetonitrile or tetrahydrofuran.
9. The process for preparing the composite plastic woven fabric according to claim 4, characterized in that: The preparation process of the TDI modified silica is as follows: adding 100 parts by weight of nano-silicon dioxide into toluene, ultrasonically dispersing, adding 60-100 parts by weight of toluene-2,4-diisocyanate, heating to 80-90° C., reacting for 2-3 hours, filtering, washing, and drying to obtain the TDI modified silica.
Citation Information
Patent Citations
Preparation of flame-retardant polyester for preparing fiber
CN101376689A
Flame retardant for polyester PET and synthesis method thereof
CN109251319A
Wear-resistant nano SiO2-polyurea in-situ modified polyimide material and preparation method thereof
CN111471175A
Synthesis method of flame-retardant nano SiO2-ultra-molecular weight polyethylene anti-puncture fiber
CN113529199A
High-performance plastic woven cloth and preparation thereof
CN117644702A
Cited By
Flame-retardant degradable polyester material and preparation method thereof
CN120757998A